Case Report: Mediastinal Mass in SARS-COV-2 Pandemic: A Word of Caution - Baisi, Alessandro; Mazzucco, Alessandra; Caffarena, Giovanni; Cioffi, Gerardo; Guttadauro, Angelo; Cioffi, Ugo (Frontiers in Surgery, 2021)
Background SARS-CoV-2 is a new disease with some manifestations not yet well known. Sharing experiences in this topic is crucial for the optimal management of the patients. Case presentation Left upper extremity deep vein thrombosis (UEDVT) due to a mediastinal mass strongly suspected of lymphoproliferative disease in a patient affected by SARS-CoV-2, disappearing at the resolution of the viral infection. Conclusion Before proceeding to surgical biopsy, mediastinal mass in SARS-CoV-2 patients must be revaluated after the resolution of the infection.